Galcanezumab-induced psoriasis-like lesions of the eyebrows: A case report and review of CGRP's role in cutaneous inflammation - Patricia Díaz-Corta; Sergio Campoy; Lidia Termens; Andrea Bauer; Jaume Campdelacreu; Joan Prat; Mariano Huerta-Villanueva; Albert Muñoz-Vendrell (Cephalalgia Reports)
Introduction Anti-calcitonin gene-related peptide (CGRP) monoclonal antibodies have shown excellent efficacy and tolerability in patients with migraine. However, their systemic side effects, particularly on the skin, where CGRP plays a key role in regulating inflammation and immune responses, are not fully understood. We present a case of psoriasiform skin lesions associated with galcanezumab. Case report A 65-year-old female with chronic migraine and medication overuse headache, with current 27 monthly migraine days (MMD) of high intensity, initiated treatment with galcanezumab after failure with onabotulinumtoxinA. Three weeks after the first dose, she developed erythema, itching, and scaling on both eyebrows, diagnosed with psoriasis-like lesions. The patient had no prior history of dermatological conditions. Despite improvement in migraine frequency (three MMD of mild intensity), the lesions persisted, leading to treatment discontinuation following three doses. Five weeks after discontinuation, the lesions resolved, but migraine worsened (22 MMD). Fremanezumab was subsequently initiated, achieving migraine control (13 MMD of mild intensity) without dermatological lesions recurrence over 12 months. Conclusion This case highlights a potential dermatological adverse effect of galcanezumab, emphasizing the need for skin monitoring in patients receiving anti-CGRP therapies. Calcitonin gene-related peptide blockade may disrupt cutaneous immune balance, triggering inflammatory conditions such as psoriasiform lesions.